2018
DOI: 10.26911/thejhpb.2018.03.04.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Comic as Learning Media to Enhance Knowledge of Menarche and Menstruation among Female Students in Yogyakarta

Abstract: Background: Menarche and menstruation are physiological process but they can cause physical, emotional discomfort, and anxiety. Menarche age tends to decline. Ignorance about menarche and menstruation may increase the risk of early pregnancy or unwanted pregnancy. This study aimed to determine the effectiveness of comic as a learning media to enhance knowledge on menarche and menstruation among female primary school students in Yogyakarta. Subjects and Method: This was a quasi-experiment with before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The BSE health education program with a blended learning strategy was useful for improving the cognitive abilities of female students at SMK Negeri 2 Yogyakarta, based on previous studies (Pratiwi, R et al, 2020). The results of our research further show that the BSE blended learning health education program has been effective in improving cognitive performance in young women at SMA Wachid Hasyim Tebuireng.…”
Section: Cognitive Variablessupporting
confidence: 63%
“…The BSE health education program with a blended learning strategy was useful for improving the cognitive abilities of female students at SMK Negeri 2 Yogyakarta, based on previous studies (Pratiwi, R et al, 2020). The results of our research further show that the BSE blended learning health education program has been effective in improving cognitive performance in young women at SMA Wachid Hasyim Tebuireng.…”
Section: Cognitive Variablessupporting
confidence: 63%
“…In this study, the change in knowledge of the comic group was greater than that of the leaflet group. Previous research has shown that giving comics is more effective as a learning medium than leaflets in increasing students' knowledge (23,26). This may be the case because comics are an interesting educational medium, with attractive pictures and colors to develop children's imaginations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with exposure to this comic, children's social skills are expected to develop optimally. A study revealed that comics have the feasibility as a medium of learning in schools (Yulianda et al, 2019) and health promotion (Nuraini & Ronoatmodjo, 2018). Another study found that comics as a learning medium have an influence on school student achievement (Siregar, 2017).…”
Section: Introductionmentioning
confidence: 99%